2021
DOI: 10.3390/ijerph18147510
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Lifestyle Exercise and Nutrition Intervention in University Employees during the COVID-19 Pandemic: A Randomized Controlled Trial

Abstract: Healthy lifestyles should be encouraged in the workplace through the occupational health teams of the companies. The objective of the present study was to evaluate the adherence to a lifestyle intervention carried out in university employees during the COVID-19 pandemic and its impact on health-related quality of life (HrQoL). A randomized controlled trial following the CONSORT guidelines was performed, consisting of three supervised interventions lasting for 18 weeks: an educational intervention on healthy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 73 publications
3
16
1
Order By: Relevance
“…In addition to representing a majority in all samples, three articles were conducted specifically with female samples [ 14 , 33 , 34 ]. Heterogeneity was identified in relation to the sample characteristics, highlighting four samples composed of participants with insufficient levels of physical activity at the baseline [ 14 , 16 , 22 , 35 ], two samples with cancer survivors [ 32 , 34 ], and two with type II diabetes patients [ 36 , 37 ]. Regarding the objectives of the studies, six articles directed interventions to physical activity [ 31 , 32 , 33 , 34 , 35 , 38 ], two studies were focused on behavioral change [ 36 , 37 ], two studies investigated a whole lifestyle [ 16 , 22 ], and one study directed actions towards physical activity and behavioral change [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to representing a majority in all samples, three articles were conducted specifically with female samples [ 14 , 33 , 34 ]. Heterogeneity was identified in relation to the sample characteristics, highlighting four samples composed of participants with insufficient levels of physical activity at the baseline [ 14 , 16 , 22 , 35 ], two samples with cancer survivors [ 32 , 34 ], and two with type II diabetes patients [ 36 , 37 ]. Regarding the objectives of the studies, six articles directed interventions to physical activity [ 31 , 32 , 33 , 34 , 35 , 38 ], two studies were focused on behavioral change [ 36 , 37 ], two studies investigated a whole lifestyle [ 16 , 22 ], and one study directed actions towards physical activity and behavioral change [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity was identified in relation to the sample characteristics, highlighting four samples composed of participants with insufficient levels of physical activity at the baseline [ 14 , 16 , 22 , 35 ], two samples with cancer survivors [ 32 , 34 ], and two with type II diabetes patients [ 36 , 37 ]. Regarding the objectives of the studies, six articles directed interventions to physical activity [ 31 , 32 , 33 , 34 , 35 , 38 ], two studies were focused on behavioral change [ 36 , 37 ], two studies investigated a whole lifestyle [ 16 , 22 ], and one study directed actions towards physical activity and behavioral change [ 14 ]. Regarding the research design, the selected studies were classified as randomized controlled trials (n = 4), intervention studies (n = 4), non-randomized controlled trials (n = 1), longitudinal (n = 1), and quasi-experimental (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference was that at the end of the diet component, the Spanish government ordered a strict stay-at-home lockdown to stop the expansion of the COVID-19 outbreak, so the physical exercise program was remotely supervised in real-time, as the participants were at home. In this exercise program, with the same characteristics as that of the ISEG, the participants performed self-loading strength exercises and performed aerobic exercise jogging at home since they did not have specific training material or large spaces [40].…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…Regarding PA, only one study managed to increase and maintain PA levels six months after in-person physical exercise intervention [39]. Another recent randomized clinical trial with a remotely supervised physical exercise and diet intervention reported a long-term improvement in physical exercise and eating habits, although without significantly increasing weekly metabolic equivalent tasks (METS)-min or adherence to the Mediterranean diet [40].…”
Section: Introductionmentioning
confidence: 99%